The influence of children's rights in the implementation of the provision of education for young prisoners in Malaysia / Rosfizah Md. Taib - Md. Taib, Rosfizah (2014)
The paper will examine the extent to which the notion of children's rights, particularly educational rights has been perceived by the Malaysia Prisons Department in relation to the provision of educational opportunities amongst young prisoners. The discussion covers the interview data from the Malaysian prison officials towards discovering why the Malaysian government has been providing educational opportunities for young prisoners. In conclusion, the findings suggest the implementation of law and policy regarding educational provision available for young prisoners in Malaysia is driven by a commitment of the government to fulfill the notion of childrens rights, particularly educational rights.